PENGARUH SUPERVISI KEPALA SEKOLAH, BUDAYA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP MUTU PEMBELAJARAN SMP NEGERI DI SUB RAYON 01 KABUPATEN PEKALONGAN - Anika Yulistyarini; Ngasbun Egar; Ghufron Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education plays an important role in improving human resources. Through education, it can create a superior and competitive generation that is qualified to face challenges in the future. This study aims to determine the effect of: 1) principal supervision on the quality of learning; 2) school culture on the quality of learning; 3) teacher work motivation on the quality of learning; and 4) principal supervision, school culture, and teacher work motivation together on the quality of learning in Public Junior High Schools in Sub Rayon 01 Pekalongan Regency. The type of research is quantitative research with a survey method. The population consists of 288 teachers of Public Junior High Schools in Sub Rayon 01 Pekalongan Regency. The sample in this study was 165 teachers selected using the proportional random sampling technique. Data collection was carried out using the questionnaire technique. Data analysis was carried out using multiple linear regression analysis. The results of the analysis show that: 1) there is a positive and significant effect of principal supervision on the quality of learning. This is indicated by the results of the statistical t test of 9,800 which is significant at α = 0.05; 2) there is a positive and significant influence of school culture on the quality of learning. This is indicated by the results of the statistical t test of 11,512 which is significant at α = 0.05; 3) there is a positive and significant influence of teacher work motivation on the quality of learning. This is indicated by the results of the statistical t test of 5,478 which is significant at α = 0.05; and 4) there is a positive and significant influence of principal supervision, school culture, and teacher work motivation together on the quality of learning at Public Junior High Schools in Sub Rayon 01 Pekalongan Regency. This is indicated by the results of the statistical F test of 1359,529 which is significant at α = 0.05. The magnitude of the influence of the variables of principal supervision, school culture, and teacher work motivation together on the quality of learning is determined by the value of the coefficient of determination (R2) produced, which is 0.961. The regression equation produced in this study is Y = -6.558 + 0.365X1 + 0.490X2 + 0.198X3 + e.